2015
DOI: 10.1371/journal.pone.0126787
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Coordination Chemistry for Nickel Chelation Motifs

Abstract: Chelation therapy is one of the most appreciated methods in the treatment of metal induced disease predisposition. Coordination chemistry provides a way to understand metal association in biological structures. In this work we have implemented coordination chemistry to study nickel coordination due to its high impact in industrial usage and thereby health consequences. This paper reports the analysis of nickel coordination from a large dataset of nickel bound structures and sequences. Coordination patterns pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Histidine binding of Ni 2+ ions is long-known and has been exploited in his-tag protein affinity purification (13). This also underlies the interaction of the major histocompatibility complex (MHC) with certain peptides (14,15), Hpn-like protein (16), in Fcg (17), and in TCRs of type IV contact dermatitis patients (18).…”
Section: Introductionmentioning
confidence: 99%
“…Histidine binding of Ni 2+ ions is long-known and has been exploited in his-tag protein affinity purification (13). This also underlies the interaction of the major histocompatibility complex (MHC) with certain peptides (14,15), Hpn-like protein (16), in Fcg (17), and in TCRs of type IV contact dermatitis patients (18).…”
Section: Introductionmentioning
confidence: 99%
“…The nickel ion has coordination numbers by four ligands34. It is reported that histidine, aspartate, glutamate and cysteine are the typically residues to coordinate nickel, among which, histidine is the most frequent over other amino acids59. Thus, further research to investigate the other potential nickel ligands is required.…”
Section: Discussionmentioning
confidence: 99%
“…However, the conserved amino acids in the nickel permease NixA of Helicobacter pylori have been described. Interestingly, next to aspartic acid, glutamic acid and histidine, which are known to be good nickelbinders [130], defined positions of serine, threonine, phenylalanine and asparagine were found to be crucial for NixA mediated uptake of nickel [131,132]. Though, these amino acids may not be directly involved in the interaction with the metal ion, but may be required for the conformation or stability of NixA.…”
Section: Biosorption and Bioaccumulation Of Cobalt And Nickelmentioning
confidence: 98%